1986
DOI: 10.1007/bf00048107
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry farming systems in the homesteads of Kerala, southern India

Abstract: Kerala State on the southwestern coast of India in the tropical humid zone has a predominantly agricultural economy, a very high density of population and therefore high pressure on cultivable land. The farmers there undertake cultivation of an array of crops -tree crops, plantation crops, seasonals and biennials -all in intimate mixtures on the same piece of land around the homesteads. Farm animals and poultry and sometimes fisheries also are essential components of the system. The close association of agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…In this region the values of homegardens as multi-purpose production systems combining ecological and socioeconomical sustainability are well recognized (Nair and Sreedharan 1986;Jose and Shanmugaratnam 1993;Kumar et al 1994). Various scientists have voiced concern that socioeconomic changes and related adoption of modernised managerial systems cause a negative conversion process of homegardens in this region (Jose and Shanmugaratnam 1993;John and Nair 1999;Santhakumar 2002).…”
Section: Study Sitementioning
confidence: 99%
“…In this region the values of homegardens as multi-purpose production systems combining ecological and socioeconomical sustainability are well recognized (Nair and Sreedharan 1986;Jose and Shanmugaratnam 1993;Kumar et al 1994). Various scientists have voiced concern that socioeconomic changes and related adoption of modernised managerial systems cause a negative conversion process of homegardens in this region (Jose and Shanmugaratnam 1993;John and Nair 1999;Santhakumar 2002).…”
Section: Study Sitementioning
confidence: 99%
“…A homestead is an operational unit in which a number of crops of which major crop is coconut are grown with livestock, poultry and fish, mainly for the purpose of satisfying the farmers basic needs. (Nair and Sreedharan, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Using artificial shading of increasing light intensity produced a relation between yield and the interception rate of the canvas. The relation is linear and can be expressed as in equation (1). Moreover, a study of gas exchanges in the plants in the different treatments showed that the amount of light received by the maize did not modify its photosynthetic response to light.…”
Section: Resultsmentioning
confidence: 99%
“…Most of this work studied the economic aspect of the intercrop combination, emphasizing the improvement in grower income [1,27]. There were few results concerning inter-and intraspecific competition.…”
Section: Introductionmentioning
confidence: 99%